Analisis Penerapan Sistem Digitalisasi Keuangan di Kantor Desa Bergolo Kecamatan Ngawen Kabupaten Blora - Al Adib, Mochammad; Susanti, Anis (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
Digitalizing village financial management has become a national priority to enhance transparency and accountability. The government, through the Ministry of Home Affairs and BPKP, promotes the use of integrated applications to ensure more orderly processes of planning, budgeting, and financial reporting, although implementation at the village level still faces technical and human resource limitations. This study analyzes the implementation of digital financial management through Siskeudes, Siskeudes Link, and CMS in Bergolo Village, Ngawen District, Blora Regency. These initiatives align with Ministry of Home Affairs Regulation No. 20/2018 and BPKP’s technical policies emphasizing transparency. However, their utilization remains suboptimal due to challenges such as limited staff competencies, uneven internet access, and incomplete system integration. Using a qualitative case study approach with interviews, observations, and documentation, the study finds that the digital applications have not fully met good governance principles and have affected the effectiveness of financial reporting and management. The findings offer insights for improving digitalization efforts at the village level.